Paediatric ART outcomes in a decentralised model of care in Cape Town, South Africa - M. M. Morsheimer; A. Dramowski; H. Rabie; M. F. Cotton (AOSIS, 2014)
Background. Although subSaharan Africa faces the world's largest paediatric HIV epidemic, only 1 in 4 children has access to combination antiretroviral therapy (ART). A decentralised approach to HIV care is advocated, but programmes in resource-limited settings encounter many challenges to community-initiated paediatric ART implementation. Methods.  A retrospective cohort analysis of 613 children receiving ART between 2004 and 2009 was performed in seven physician-run primary healthcare (PHC) clinics in Cape Town. Baseline characteristics, serial CD4+, viral load (VL) levels and status at study closure were collected. Results. Two subgroups were identified: children who were initiated on ART in a PHC clinic (n=343) and children who were down-referred from tertiary hospitals (n=270). The numbers of children initiated on ART in PHC increased sevenfold over the study period. Down-referred children were severely ill at ART initiation, with higher VLs, lower CD4+ counts and higher rates of tuberculosis co-infection (25.3% v. 16.9%; p=0.01). Median time to virological suppression was 29 weeks in PHC-ART initiates and 44 weeks in children down-referred (p<0.0001). Children down-referred to PHC either maintained or gained virological suppression. Longitudinal cohort analysis demonstrated sustained VL suppression >80%, high rates of immune reconstitution and low mortality.Conclusions. Increasing numbers of children are initiated on ART in PHC settings and achieve comparable immunological, virological and survival outcomes, suggesting successful decentralisation of paediatric HIV care. Down-referral of children with adherence-related virological failure may assist with attainment of virological suppression and sparing use of second-line medications.